Pneumocystis Jirovecii Pneumonia in a Kidney Transplant Recipient 13 Months after Transplantation: A Case Report and Literature Review - Varnas, Dominykas; Jankauskienė, Augustina (Acta medica Lituanica, 2021)
Background. Pneumocystis jirovecii pneumonia (PCP) is an opportunistic and prevalent fungal infection in immunocompromised hosts, including patients after kidney transplantation (KTx). It is a life threatening infection. While with effective prophylaxis it became less common, it still remains an issue among solid organ transplant (SOT) recipients during the first year. There are no specific clinical signs for PCP. Computed tomography (CT) is a better method for detecting PCP, but definite diagnosis can only be made by identification of the microorganism either by a microscopy or by a polymerase chain reaction (PCR).Clinical case. We present a case of a 17 year old with severe PCP 13 months after KTx followed by reduction in kidney function and respiratory compromise. The pathogen was detected by PCR from bronchoalveolar lavage fluid (BALF) and patient was treated successfully with trimethoprim-sulfamethoxazole (TMP-SMX). Patient’s condition, respiratory status and kidney function gradually improved. Our presented case is unusual because patient had no known risk factors for PCP and he was more than one year after KTx, what is considered rare. In addition patient and his parents delayed in notifying the treating physician about ongoing symptoms because did not deem them important enough.Conclusions. Clinicians treating patients in risk groups for PCP must always remain vigilant even in era of effective prophylaxis. The vigilance should also extend to the patient and patient’s family.
Keywords: Pneumocystis jirovecii; Pneumocystis pneumonia; Kidney transplant recipients; case report